(untitled) - Swann, Micheal (Mason, OH, USA, 2007)
Authors assumes that students are already intuitively familiar with many economic concepts through their own life experiences. These life experiences are then explained to students as economic concepts with clear and interesting exposition, relevant case studies, and a clean focused design. The text's major applications take the form of case studies that are meant to be read and therefore are integrated into the flow of each chapter. With this eighth edition, the book's well-crafted approach is enhanced with resources--such as Aplia and CengageNOW--that will help your students improve their understanding and will help you streamline tasks and save valuable time.
Keywords: Microeconomics,Kinh tế học vi mô